Adverse effects of nitrogenous compounds on nitrogen-fixing cyanobacterium Anabaena solitaria Klebahn (Bangladesh Journal of Botany, 2020)
The nitrogen-fixing heterocystous cyanobacterium Anabaena solitaria was tested for its response to different concentrations of nitrogen sources, namely nitrate and ammonia. To compare both the effect of concentration and type of nitrogen source, gradual concentrations were prepared for both ammonia and nitrate. The results showed concentration was significantly important on the frequency of heterocyst formation where highest nitrogen compounds concentrations were inhibitory for heterocyst formation. On the other hand, the effect of the type of nitrogenous compounds tested was insignificant which only proves that they are equally usable by cyanobacteria which will use them instead of transforming one of its cells to heterocyst thus not performing nitrogen fixation. Results also revealed the massive growth of heterotrophic bacteria in presence of nitrogenous compounds. This indicates that the presence of nitrogenous compounds in fields in which nitrogen-fixing cyanobacteria are to be used as biofertilizers can be inhibitory for nitrogen fixation and stimulatory for heterotrophic bacterial growth which could be pathogenic and harmful to plants. The use of more nitrogen-fixing cyanobacteria with the minimum amount of nitrogenous compounds is recommended.